Bauran Pemasaran Amygdala Bamboo Dalam Mengenalkan Kerajinan Bambu Modern - Santi Susanti; Pandu Watu Alam (Benefit: Jurnal Manajemen dan Bisnis, 2025)
This research aims to reveal the marketing mix applied by Amygdala Bamboo in marketing modern bamboo handicraft products to potential buyers. A descriptive qualitative method is used in this study. Primary data was obtained through interviews with the owner of Amygdala Bamboo, Harry Mawardi, and non-participatory observations at the production site of the Amygdala’s works in Mekarsari Village. Secondary data is collected through online and offline literature reviews and documents. The findings indicate that Amygdala’s bamboo crafts are produced in collaboration with bamboo artisans in Selaawi, Garut Regency. The unique designs give Amygdala Bamboo products a higher market value than existing bamboo products, enabling them to penetrate modern markets and increasing the income and welfare of the bamboo artisans in Selaawi who collaborate with Harry. Amygdala Bamboo applies the 4P marketing elements—product, price, place, and promotion—along with packaging to reach a wider audience. Instagram, YouTube, and Facebook are promotional media for Amygdala Bamboo products.